2012
DOI: 10.1074/jbc.m111.313700
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mechanism of Sep-tRNA:Cys-tRNA Synthase

Abstract: Background: SepCysS catalyzes the conversion of tRNA-bound O-phosphoserine to Cys. Results: Three Cys residues are essential for SepCysS activity, and two of them form disulfide and persulfide intermediates. Conclusion: SepCysS transfers sulfur through generating disulfide and persulfide enzyme adducts. Significance: Elucidation of the sulfur transfer mechanism of SepCysS is crucial for understanding the tRNA-dependent Cys biosynthesis and sulfur metabolism in methanogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…It has also been shown that free Cys is not synthesized independently of tRNA Cys in Methanococcus maripaludis (5), consistent with later findings showing that, in contrast to aerobic cells, neither Hcy nor iron-sulfur clusters are synthesized with sulfur originating from Cys in that organism (6). Studies of SepCysS expressed in Escherichia coli suggested that the enzyme does not efficiently use sulfide as a sulfur source in vitro (7) but instead consumes sulfane from persulfide to form Cys-tRNA Cys (7,8) (Fig. 1).…”
supporting
confidence: 78%
“…It has also been shown that free Cys is not synthesized independently of tRNA Cys in Methanococcus maripaludis (5), consistent with later findings showing that, in contrast to aerobic cells, neither Hcy nor iron-sulfur clusters are synthesized with sulfur originating from Cys in that organism (6). Studies of SepCysS expressed in Escherichia coli suggested that the enzyme does not efficiently use sulfide as a sulfur source in vitro (7) but instead consumes sulfane from persulfide to form Cys-tRNA Cys (7,8) (Fig. 1).…”
supporting
confidence: 78%
“…Although the exact mechanism of the SepCysS-catalyzed reaction has not yet been fully elucidated, the Sep-to-Cys conversion most likely proceeds through a PLP-dependent generation of a dehydroalanyl-tRNA Cys intermediate, which is subsequently attacked by a persulfide group to form Cys-tRNA Cys ( 60 , 61 ). Both “ Ca .…”
Section: Resultsmentioning
confidence: 99%
“…Both “ Ca . Parcubacteria” and Chloroflexi SepCysS possess residues involved in PLP binding ( 59 ), while only Chloroflexi SepCysS harbors conserved Cys residues implicated in persulfide ( 60 , 61 ) and Fe−S cluster formation ( 6 ). “ Ca .…”
Section: Resultsmentioning
confidence: 99%